Releasing iron from ferritin protein nanocage by reductive method: The role of electron transfer mediator - Koochana, Prashanth Kumar; Mohanty, Abhinav; Das, Suman; Subhadarshanee, Biswamaitree; Satpati, Suresh; Dixit, Anshuman; Sabat, Surendra Chandra; Behera, Rabindra K. (Biochimica et biophysica acta. General subjects, 2018)
Ferritin detoxifies excess of free Fe(II) and concentrates it in the form of ferrihydrite (Fe2O3·xH2O) mineral. When in need, ferritin iron is released for cellular metabolic activities. However, the low solubility of Fe(III) at neutral pH, its encapsulation by stable protein nanocage and presence of dissolved O2 limits in vitro ferritin iron release. Physiological reducing agent, NADH (E1/2 = −330 mV) was inefficient in releasing the ferritin iron (E1/2 = +183 mV), when used alone. Thus, current work investigates the role of low concentration (5–50 μM) of phenazine based electron transfer (ET) mediators such as FMN, PYO - a redox active virulence factor secreted by Pseudomonas aeruginosa and PMS towards iron mobilization from recombinant frog M ferritin. The presence of dissolved O2, resulting in initial lag phase and low iron release in FMN, had little impact in case of PMS and PYO, reflecting their better ET relay ability that facilitates iron mobilization. The molecular modeling as well as fluorescence studies provided further structural insight towards interaction of redox mediators on ferritin surface for electron relay. Reductive mobilization of iron from ferritin is dependent on the relative rate of NADH oxidation, dissolved O2 consumption and mineral core reduction, which in turn depends on E1/2 of these mediators and their interaction with ferritin. The current mechanism of in vitro iron mobilization from ferritin by using redox mediators involves different ET steps, which may help to understand the iron release pathway in vivo and to check microbial growth. PMS and PYO releases more iron from ferritin nanocages than FMN. Ferritin protein nanocages synthesize ferrihydrite mineral core in their central cavity. Pyocyanin (PYO), a microbial virulence factor and PMS mobilized more iron as compared to FMN, owing to their better ET relay ability (faster rate of NADH oxidation, dissolved O2 consumption, and mineral core reduction). Inset: simultaneous monitoring of dissolved O2 consumption (left Y-axis) and % of iron released (right Y-axis) in the form of Fe(II)-ferrozine complex from frog M ferritin during the reductive pathway. [Display omitted] •PYO & PMS release more iron from ferritin as compared to FMN, in presence of NADH.•Unlike FMN, PYO & PMS do not exhibit two distinct phases of iron release.•PYO can release significant amount of iron even in the presence of dissolved O2.•Electron relay (from NADH to ferritin iron) ability of mediators enhance iron release.•Reductive mobilization of ferritin iron may help to check microbial growth.